A COMPUTER TECHNIQUE FOR ANALYZING RADIO‐TELEMETRY DATA - Gregory. T. Koeln (Wildlife Society Bulletin)
Abstract An interactive computer system to analyze radio‐telemetry data has been developed and used on turkey observations. The program calculates home range by the convex polygon, capture radius, and non‐circular home range methods. Geometric center of use, total and daily travel distance, circumference of the area of use, and mean activity radius are also calculated. Users are able to select appropriate computer graphics of animal movements, home ranges, geometric center locations, and habitat map overlays. minimum inputs to the system include: animal identification number, code for the known‐location from which the readings are made, time of day, azimuth direction from station to animal, date, and the x‐y coordinates for each known‐location. Coordinate systems such as the Universal Transverse Mercator System, the State Plane Coordinate System, Or any user defined system with equal size units in north‐south and east‐west directions may be used. The system is designed to reduce the time from collection of field data to the final analysis, improve accuracy of the analysis, make graphical displays of the data, and allow access to the data for future use.